User Experience of The Academic Community in The Islamic Library and Information Science Study Program at UIN SMH Banten on Digital Library Applications Using The Webqual 4.0 Method - Saputra, Dwi Fajar; Pujawati, Tesa; Al Meida, Adelia; Khadijah, Amanah Siti (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
As time goes by, technology is also developing rapidly, making everything digital, including libraries, which are also experiencing developments where all library collections have been digitized. Conventional libraries have become digital libraries. One application that has many digital collections is iPusnas. This national digital library has a collection of 73,302 book titles and 891,397 ebook copies, which can be downloaded and installed on Playstore/Appstore. This research aims to determine user satisfaction with the iPusnas application based on user experience. This research method uses quantitative methods. The data collection techniques in this research are literature study and questionnaire data. The data analysis technique uses the Webqual 4.0 method. The results of this research are that respondents are very satisfied with the iPusnas application and do not experience problems when logging in. Many also agree that the queue to borrow collections on the iPusnas application is very long. Hence, the writer/researcher wants to suggest increasing the number of copies of books (ebooks) that people can read—users of the iPusnas application.